Cabildos eclesiásticos y clero catedralicio en el Antiguo Régimen: estado de la cuestión - Díaz Rodríguez, Antonio J. (2013)
At the end of the first decade of the 21st century, it seems to be a fitting moment to stop and analyse the current status of the issue of ecclesiastical chapters in the catholic Atlantic World. So in the present paper I make available to the reader a review of the main historiographic production in a summary and comparative way, with special attention to the spanish bibliography, but without ignoring that of other countries like France, England, Germany, Italy, Portugal, Mexico or Peru, for example.